An inquiry into the Japanese mind as mirrored in literature : - Tsuda, Sōkichi (Apan Society for the Promotion of Science, 1970)
This volume represents an exhaustive history of Japanese literature and thought during the period following the Age of the Samurai, when the common people gradually assumed a powerful influence over society and the national economy and came to be the new principal force in cultural development. Dissatisfied with conventional works on the history of Japanese literature, Tsuda made a new attempt to examine literature from an ideological point of view, focusing his analysis on the thought-content expressed in each literary work. His inquiry encompasses fine arts, music, and religion, as well as strictly literary works, making this an invaluable cultural history of the period and an incisive analysis of the Japanese national mind during a period of great transformation and change.